La tecnologia robotica può salvare I beni culturali sommersi? - Ramiro Dell'Erba (mediaGEO soc. coop., 2018)
Cultural Heritage can largely profit from the set of technologies that have recently been developed in Submarine Robotics. In this paper, we focus on how underwater robotics and related technologies can be used to enhance economical fruition, control, protection and social impact of the cultural heritage.